(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This comprehensive review delves into the characteristics and fundamental theorems governing analytic and univalent functions, pivotal concepts in complex analysis. Analytic functions, defined by their ability to be locally represented by convergent power series, play a crucial role in various branches of mathematics and physics. Univalent functions, a subset of analytic functions, are valued in the unit disk and are one-to-one mappings. The review covers key topics such as the Riemann mapping theorem, which asserts the existence of a conformal map between simply connected regions in the complex plane, and the coefficient bounds for univalent functions, which provide insights into their geometric properties. Additionally, it explores the connection between univalent functions and geometric function theory, examining criteria for univalence and related classes like starlike and convex functions. Recent developments in the field, including applications of analytic and univalent functions in mathematical physics, biology, and engineering, are also discussed. The article emphasizes the importance of these functions in understanding complex phenomena and their utility in modeling real-world problems. This review aims to provide a structured overview of the theoretical underpinnings, significant theorems, and practical implications of analytic and univalent functions, appealing to mathematicians, physicists, and researchers interested in complex analysis and its applications.